Analysis of Digital Literature on Students in Faculty of Teacher Training and Education as a Prospective Teacher - Nuril Huda; Ninik Mardiana; Sumartono (HM Publisher, 2022)
This research is to reveal how the ability to use and understand digital literacy of students as prospective teachers in FKIP. This is in line with the digital literacy program launched by the Ministry of Education and Culture in 2018. The method used is descriptive quantitative. As the main data in the form of student questionnaire answers that utilize electronic questionnaire instruments distributed through social media. The population of this research is active students at FKIP University Dr. Soetomo Surabaya with a sample size of 140 is random sampling, with an error rate of 4.5%. Data analysis by converting the attitude scale in a value scale of 1-5, to calculate the average value as a generalization of the research results. The results showed that the students' ability in digital literacy was at a level between quite capable and capable. As for those who have reached the fully capable level in the aspects of using search engines of data, creating good communication on the internet, especially on social media, and understanding the existence of internet ethics, copyright issues and plagiarism.